Fractal signatures of the COVID-19 spread. (November 2020) - Abbasi, M.; Bollini, A.L.; Castillo, J.L.B.; Deppman, A.; Guidio, J.P.; Matuoka, P.T.; Meirelles, A.D.; Policarpo, J.M.P.; Ramos, A.A.G.F.; Simionatto, S.; Varona, A.R.P.; Andrade-II, E.; et al.
Highlights: Identification of the signatures of the fractal structure on real data. New SIR-like model that includes the fractal structure in the spread of the virus. Analysis performed on data observed in several regions around the world. Time evolution analysis using the newly developed model. Abstract: Recent quantitative approaches for studying several aspects of urban life and infrastructure have shown that scale properties allow the understanding of many features of urban infrastructure and of human activity in cities. In this paper, we show that COVID-19 virus contamination follows a similar pattern in different regions of the world. The superlinear power-law behavior for the number of contamination cases as a function of the city population, with exponent β of the order of 1.15 is always obtained. Due to the strong indication that scaling is a determinant feature of covid-19 spread, we propose an epidemiological model that embodies a fractal structure, allowing a more detailed description of the observed data about the virus spread in different countries and regions. The hypothesis that fractal structures can be formed in cities as well as in larger networks is tested, indicating that indeed self-similarity may be found in networks connecting several cities.